Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Dalam Penetapan Harga Jual Dengan Cost Plus Pricing (Studi Kasus UMKM Tempe di Kabupaten Langkat) - Prisna, Nila Dera; Hermain, Hendra; Indra, Ahmad Perdana (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This research was conducted with the aim of knowing how to calculate the cost of production using the full costing method in determining the selling price using cost plus pricing for Tempe UMKM in Langkat Regency. The research method used in this research is a descriptive qualitative method. Sources of data used are primary data and secondary data. The data collection techniques used are observation, interviews and documentation. The results showed that the calculation of the cost of production using the full costing method was higher than the method used by MSME owners. According to the full costing method, the cost of producing tempe per gram is Rp. 9, while according to the MSME owner's method, the cost of producing tempe per gram is Rp. 8.98. Calculating the selling price using the cost plus pricing method produces a higher price than the price set by MSME players. Tempe measuring 70 grams costs IDR 835/pcs, tempe measuring 120 grams costs IDR 1,432/pcs, tempe measuring 150 grams costs IDR 1,789/pcs, tempe measuring 350 grams costs IDR 4,175/pcs. Whereas the price applied by MSME actors for tempe measuring 70 grams costs Rp. 700/pcs, tempe measuring 120 grams costs Rp. 1,250/pcs, tempe measuring 150 grams costs Rp. This difference in selling prices occurs because the cost plus pricing method has added a profit of 30% as expected by MSME players.